2007
DOI: 10.1111/j.1600-0463.2007.apm_514.x
|View full text |Cite
|
Sign up to set email alerts
|

Reactive oxygen species and antioxidant mechanisms in human tissues and their relation to malignancies

Abstract: Reactive oxygen species (ROS) are formed in mammalian cells as a consequence of aerobic respiration. Despite multiple conserved redox modulating systems, a given proportion of ROS continuously escape from the mitochondrial respiratory chain, being sufficiently potent to damage cells in various ways, including numerous carcinogenic DNA mutations. Oxidative stress resulting from an imbalanced ratio between ROS production and detoxification may also disturb physiological signal transduction, lead to chain reactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
221
0
12

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 296 publications
(237 citation statements)
references
References 207 publications
(229 reference statements)
4
221
0
12
Order By: Relevance
“…8-OxodG is one of the most widely used biomarkers of oxidative stress, mainly because of its abundance in DNA and also (Karihtala and Soini, 2007). Compared with other bases, guanine most readily undergoes an oxidative attack in the presence of ROS (Peoples and Karnes, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8-OxodG is one of the most widely used biomarkers of oxidative stress, mainly because of its abundance in DNA and also (Karihtala and Soini, 2007). Compared with other bases, guanine most readily undergoes an oxidative attack in the presence of ROS (Peoples and Karnes, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…These reactions in connection with oncogenes or tumour suppressor genes may result in the initiation of cancer (Loft and Poulsen, 1996). Several recent studies have shown high ROS levels in carcinoma cells compared with the surrounding healthy tissue (reviewed in Karihtala and Soini, 2007). Under normal conditions, ROS are maintained within narrow boundaries by scavenging systems, such as superoxide dismutases, peroxiredoxins (Prx) and glutathione-related antioxidant defences.…”
mentioning
confidence: 99%
“…The formation of ROS and especially hydroxyl radical leads to reactions with DNA, proteins and lipids inducing mutations and cellular damage. 5,6 As a consequence of these reactions, high levels of iron have been identified as a risk factor for the development of cancer. 7,8 Several pathways for iron-induced carcinogenesis have been proposed.…”
Section: Dear Editormentioning
confidence: 99%
“…The representative antioxidant proteins identified in the cEOC include glutathione S-transferases, peroxidases, and superoxide dismutases, and activation of protective genes, including those encoding the heat shock proteins (8,12,13,22). On the contrary, enhanced antioxidant mechanisms have been implicated in chemoresistance and lead to poor prognosis (23). ROS effects can be silenced by high concentrations of antioxidants, whereas in some cells with damaged mitochondria, the opposite effect is possible (24).…”
Section: Pro-oxidative and Antioxidative Balance In Ceocmentioning
confidence: 99%